The pragmatics of discourse coherence : theories and applications - Gruber, Helmut, 1928-; Redeker, Gisela (Pragmatics & beyond, 2014)
Based on a corpus of Austrian students' texts from three disciplines (personnelmanagement, business psychology, economic history) analysed with RhetoricalStructure Theory (RST), this paper investigates the macro-structural expectationswhich tables of content (ToCs) raise, the cues by which these expectationsare triggered, and the "predictive quality" of ToCs. The ToCs in the personnelmanagement group's texts offer the best "prediction" of the actual macrostructures, whereas in the other two groups ToC and textual macro-structuresdiverge from each other in various ways. The analysis also shows a